THE ROLE OF PEDAGOGICAL TECHNOLOGIES IN ENGLISH LESSONS - Toshaliyeva Xursanoy; Igamberdieva Shahnoza (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
This article emphasizes the importance of foreign languages in the Republic of Uzbekistan and the need to study them, highlights innovative technologies. Pedagogical technology is a set of methods, techniques, techniques, directions and principles that increase the effectiveness of the lesson and the activities of students in the classroom.